Analysis on the treatment of acne by Sanhuang with network pharmacology and experimental research - Ju PENG; Yan WANG; Zhancao LI; Xi LUO; Jun SHI; Limin ZHAO; Ping ZHAO (KeAi Communications Co., Ltd., 2022)
[Abstract]: Objective: To explore the main active components and potential targets of "Sanhuang Xiexin decoction" (Sanhuang) against acne based on network pharmacology and molecular docking technology, and research the bacteriostatic mechanism by biochemical experiments. Methods: Pharmacological database and Analysis platform of the Traditional Chinese Medicine System (TCMSP) and SwissTarget database were used to obtain the active components and the targets of Sanhuang in the treatment of acne, respectively. The acne-related targets were screened by OMIM, GeneCards, and DisGeNET databases, and the interaction targets were analyzed by Cytoscape and String databases, followed with enrichment analysis by Genome Encyclopedia (KEGG) and Gene Ontology (GO). The predicted results were validated by molecular docking. The bacteriostatic zones of Sanhuang to acne were determined by Oxford cup method, and the minimum bacteriostasis concentration was obtained by double dilution method. The bacteria morphology change in the presence of Sanhuang was observed by scanning electron microscope and the ionic leakage rate was detected to reflect the permeability of bacterial cell walls. Finally, the IL-6 expression of drug-treated acne was determined. Results: From Rheum palmatum L, Coptis chinensis Franch, and Scutellaria baicalensis Georgi, 34, 25 and 44 active ingredients were selected, and 145, 216 and 163 compound targets were screened out, respectively. There are 123 intersection targets of Sanhuang and acne, which mainly function through IL-17, MAPK, PI3K-Akt, and TNF signaling pathways. Molecular simulation results showed that aloe-emodin and quercetin in Coptis Chinensis Franch had strong affinities with the core targets of TNF, IL-6, INS, and AKT1. The antibacterial zones of Sanhuang at concentrations of 0.1 g/mL and 0.5 g/mL were (21.0±0.3) mm and (26.1±0.9) mm, respectively, which had an obvious dose-dependent relationship. The minimum inhibitory concentration of Sanhuang was 4 mg/mL. Moreover, in the drug-treated acne, the morphology of bacterial cells was destroyed, the permeability of cell walls was increased, and the growth of propionibacterium acnes was inhibited. The results of cell experiment showed that Sanhuang inhibited the expression of IL-6. Conclusion: Based on network pharmacology method, we predicted the mechanism of Sanhuang in the treatment of acne which was charactered by multi-component, multi-target, and multi-pathway, and verified the therapeutic effect of Sanhuang on acne by the biochemical method such as bacteriostasis test and cell experiment. Sanhuang can inhibit the growth of Propionibacterium acnes mainly by regulating the target genes such as TNF, IL-6, INS, and AKT1.